О ПРОИСХОЖДЕНИИ ЛИТИЙ-ФТОРИСТЫХ ГРАНИТОВ СЕВЕРНОГО МАССИВА (ЧУКОТКА) - Алексеев В.И. (My University, 2005)
Two groups of rocks have been distinguished in Scvemy intrusive massif (Chukotka peninsula) and their mineralogy was compared: biotite granites, forming the major volume of the massif, and the group of zinnwalditc granites including ongonite-likc microgranilc porphyries developed over limited areas and never remarked in the massif before. Under the carried out investigation, the biotite granites show (he mctasomatic nature of their mincraiogic-gcochc-mical peculiarities, thus, becoming similar to the rare-metal lithiumfluorinc granites. Abundance of grciscai/ed granites over the whole massif can be related to geological conditions of localization of zinnwalditc granitoids intruded into biotite granites. It was proved that topaz- and zinmvaldite-bcunng albitc granites have magmntic origin. Suppo- ucocheniica! tvne ol sub;
Keywords: 549.1:552.321(571.651)